Implementation of SAK EMKM on the Quality of KunciKu MSME Financial Reports - Jauhariah Al-Islam Inayatulah; Laylan Syafina; Yenni Samri Julianti Nasution (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
The preparation of the financial reports for UMKM KunciKu has not followed the standards for preparing SAK EMKM financial reports because of a problem faced by UMKM KunciKu, namely regarding the UMKM owners not understanding the SAK EMKM, difficulties when presenting financial reports and time constraints when presenting financial reports and time constraints when presenting financial reports. The government regulates SAK EMKM as a regulation tht has been ratified by DSAK-IAI, in order to make it easier for MSME owners when recording out in order to obtain information and understand the problems experienced by KunciKu MSMEs when making financial reports in line with SAK EMKM. The research process that researchers use is a qualitative research process. The process of collecting information through observation, interview, documentation and literature study. The research results stated that the preparation of financial reports presented by KunciKu MSMEs had not implemented SAK EMKM and the MSMEs only made ordinary financial reports that could only be understood by MSME owners. This research is important to carry out in order to make MSME players aware tht financial reports tht are in line with SAK EMKM can make things easier for MSME players.